2021
DOI: 10.1001/jamacardio.2021.0939
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients With Heart Failure With Recovered Ejection Fraction

Abstract: Heart failure with recovered ejection fraction (HFrecEF) is a recently recognized phenotype of patients with a history of reduced left ventricular ejection fraction (LVEF) that has subsequently normalized. It is unknown whether such LVEF improvement is associated with improvements in health status.OBJECTIVE To examine changes in health-related quality of life in patients with heart failure with reduced ejection fraction (HFrEF) whose LVEF normalized, compared with those whose LVEF remains reduced and those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Several studies have confirmed recovered or improved ejection fraction as an independent group associated with reduced adverse events, such as cardiovascular death and hospitalization, compared with both HFrEF and HFpEF patients ( 5 , 6 ). In addition to the effect on mortality and hospitalization outcomes, Peter Wohlfahrt et al confirmed that HFrecEF significantly improved the quality of life in patients with heart failure ( 9 ). However, the prognostic effect of recovered ejection fraction was inconsistent or even non-significant ( 10 , 12 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed recovered or improved ejection fraction as an independent group associated with reduced adverse events, such as cardiovascular death and hospitalization, compared with both HFrEF and HFpEF patients ( 5 , 6 ). In addition to the effect on mortality and hospitalization outcomes, Peter Wohlfahrt et al confirmed that HFrecEF significantly improved the quality of life in patients with heart failure ( 9 ). However, the prognostic effect of recovered ejection fraction was inconsistent or even non-significant ( 10 , 12 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous HFrEF patients who developed HFimpEF during the follow-up visit were demonstrated with not only a better prognosis but also a significant improvement in health-related quality of life ( 6 , 9 ). However, different conclusions appeared in Joan Carles Trullàs's study, which showed that the risk of death between HFimpEF and HFrEF groups was not statistically significant ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…baseline LVEF of ≤40% that improved to LVEF ≥50% during the study period). 22 24 Similarly, in a large study of patients with and without HF in the National Echo Database Australia, both positive and negative changes in LVEF over time were associated with increased or decreased all-cause mortality, respectively. 15 To our knowledge, no prior studies used multicentre, observational data to specifically evaluate the association between observed improvements in LVEF and in health status in large numbers of patients.…”
Section: Discussionmentioning
confidence: 97%
“…For example, investigators at the University of Utah compared changes in KCCQ‐12 scores over time for patients with HFrEF or HF with preserved ejection fraction (HFpEF) with no improvement in LVEF to changes in KCCQ‐12 in patients that had HF with recovered ejection fraction (i.e. baseline LVEF of ≤40% that improved to LVEF ≥50% during the study period) 22 . Among 35 patients that had HF with recovered ejection fraction, the mean change in KCCQ‐12 score was 15.3 (standard deviation 19.9) compared with 5.8 (20.2) in the HFrEF group and 2.2 (19.8) in the HFpEF group ( p =0.009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation